Encyclopedia of Inorganic and Bioinorganic Chemistry 2012
DOI: 10.1002/9781119951438.eibc0247.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Metals: Organometallic ChemistryUpdate based on the original article by Jacob S. Alexander, Marites Guino‐o, Maria Felisa Zuniga, Roger C. Hahn and Karin Ruhlandt‐Senge,Encyclopedia of Inorganic ChemistrySecond Edition, © 2005, John Wiley & Sons, Ltd.

Abstract: The organometallic chemistry of the alkaline‐earth metals has undergone a renaissance during the last 20 years with heavy organoalkaline‐earth metal compounds becoming recognized as an area of organometallic chemistry with significant potential. Intense research efforts have provided a series of synthetic methodologies that provided access to a rapidly growing family of compounds not thought possible only recently. As a result, this improved insight did not only provide the basis for a more detailed understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 271 publications
0
3
0
Order By: Relevance
“…β-Diketiminate ligands are clearly superior for stabilizing heteroleptic complexes. [1,[3][4][5][6][7]10] For the smaller Ae metal Mg we succeeded in isolating a heteroleptic complex. The deprotonation of [(tBu 3 Si) 2 N 3 ]H by MgnBu 2 in benzene at room temperature is instantaneous.…”
Section: Heteroleptic Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Diketiminate ligands are clearly superior for stabilizing heteroleptic complexes. [1,[3][4][5][6][7]10] For the smaller Ae metal Mg we succeeded in isolating a heteroleptic complex. The deprotonation of [(tBu 3 Si) 2 N 3 ]H by MgnBu 2 in benzene at room temperature is instantaneous.…”
Section: Heteroleptic Complexesmentioning
confidence: 99%
“…[42] From this it can be concluded that the steric pressure of the (tBu 3 Si) 2 N 3 Scheme 2. Synthesis of the triazene proligand [(tBu 3 Si) 2 N 3 ]H and conversion into s-block metal complexes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Heteroleptic Complexesmentioning
confidence: 99%
See 1 more Smart Citation